2022
DOI: 10.1002/cre2.527
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different concentrations of titanium dioxide and copper oxide nanoparticles on water sorption and solubility of heat‐cured PMMA denture base resin

Abstract: Objectives: This study aimed to evaluate the effect of different concentrations of titanium dioxide (TiO 2 ) and copper oxide (CuO) nanoparticles on the water sorption and solubility of heat-cured polymethyl methacrylate (PMMA).Materials and Methods: Fifty disc-shaped specimens (10 × 2 mm) of heat-cured PMMA were prepared and divided into five groups (n = 10) to be modified with 2.5 wt.% or 7.5 wt.% of either TiO 2 or CuO nanoparticles. One group was left unmodified, serving as the control group. Water sorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Titanium dioxide powders have assortments of applications, attributable to its ability to bestow whiteness furthermore, darkness to different things, including paints, papers,and beauty care products. The titanium dioxide has acquired incredible consideration as a promising photocatalyst because of its useful properties among the other photocatalysts, high compound strength, and minimal expense 15 , 16 . The numerous researchers presented titanium dioxide tiny particles used for the treatment of dangerous cancers types 17 and many other aspect of human daily life 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Titanium dioxide powders have assortments of applications, attributable to its ability to bestow whiteness furthermore, darkness to different things, including paints, papers,and beauty care products. The titanium dioxide has acquired incredible consideration as a promising photocatalyst because of its useful properties among the other photocatalysts, high compound strength, and minimal expense 15 , 16 . The numerous researchers presented titanium dioxide tiny particles used for the treatment of dangerous cancers types 17 and many other aspect of human daily life 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Zirconium nanoparticles (nano-ZrO2) were seen as very common nanoparticles used as additives in the modification of PMMA in a majority of the papers (27)(28)(33)(34)(35)(36)(37)(38)(39). Another composite that enhanced the PMMA was titanium dioxide (TiO2) (29,37,39). Additionally, several studies used E-glass nanoparticles as an additional composite for PMMA (27,37,39).…”
Section: Resultsmentioning
confidence: 99%
“…The solubility reflects the mass of soluble substances in the polymer. In denture-based acrylic resins, these soluble substances include initiators, activators, plasticizers, and residual monomers [ 27 ]. Previous studies have shown that the water absorption capacity of different types of acrylic resins can reach 10–25 μg/mm 3 .…”
Section: Discussionmentioning
confidence: 99%